Osmolality and carbohydrate composition of latex determine latex flow characters in Hevea brasiliensis - Gopalakrishnan J; Annamalainathan K; Thomas M (National Conference on Tree Improvement Research in India: Current Trends and Future Prospects, 2-3 February 2017, Institute of Wood Science and Technology, Bengaluru, India. Abstracts. p.98.)
Laticifers enriched phloem turgor pressure is considered as an indicator of latex yield potential in rubber clones. Generally latex production is reduced under low soil moisture and high vapour pressure density during summer months. A clone with high rate of osmoregulation in laticiferous tissue maintains turgor at low water potential. Phloem osmolality has important role in various physiological processes in plants and helps to maintain basic cellular metabolic processes and growth. Hence a study was conducted to recognize the variations in osmolality and soluble sugar composition in the latex and their contribution to osmolality leading to latex yield in different clones of Hevea brasiliensis. Latex osmolality is controlled by variable solute composition. Out of eight clones studied, clones such as PB 311, RRII 105, RRII 118 and RRIM 600 recorded high latex carbohydrate composition where as RRII 43 recorded the lowest. Contribution of solutes to the latex osmotic concentration varied significantly between peak yielding and stress seasons. The major solute contributing to the total measured osmolality of latex is found to be inositols. Significant varietal and seasonal variations were observed for its contribution to total osmolality. The results indicated a high level latex osmolality and inositiol composition in relatively drought resistant clones during stress season. Distinguishing clones with better growth/yield potential and stress resistance is essential for the extension of cultivation to marginally suitable regions.
Keywords: Hevea brasiliensis; Latex; Osmolality; Osmoregulation